Associations of hemoglobin A1c with cognition reduced for long diabetes duration - Jeremy M. Silverman; James Schmeidler; Pearl G. Lee; Neil B. Alexander; Michal Schnaider Beeri; Elizabeth Guerrero‐Berroa; Rebecca K. West; Mary Sano; Martina Nabozny; Carolina Rodriguez Alvarez (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Associations of some risk factors with poor cognition, identified prior to age 75, are reduced or reversed in very old age. The Protected Survivor Model predicts this interaction due to enhanced survival of those with extended risk factor duration. In a younger sample, this study examines the association of cognition with the mean hemoglobin A1c risk factor over the time at risk, according to its duration. Methods The interaction of mean hemoglobin A1c (average = 9.8%), evaluated over duration (average = 116.8 months), was examined for overall cognition and three cognitive domains in a sample of 150 “young‐old” veterans (mean age = 70) with type 2 diabetes. Results The predicted interactions were significant for overall cognition and attention, but not executive functions/language and memory. Discussion Findings extend the Protected Survivor Model to a “young‐old” sample, from the very old. This model suggests focusing on individuals with good cognition despite prolonged high risk when seeking protective factors.